Convergence of the Labour Productivity in European Union Agriculture - Joanna Jaroszewska; Robert Pietrzykowski (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The objective of the paper is to examine the changes in the level of diversification of the labour productivity in the European Union countries in the years 1998-2015, and then to determine whether there is any convergence of the labour productivity among these countries. The labour productivity has been calculated as a relation of the gross value added at constant prices per one full-time employee. The study used the Economic Accounts for Agriculture (EAA) and the Agricultural Labour Input (ALI). The study covered the European Union countries, broken down by the countries of the „old” EU (EU-15) and the countries admitted to the EU after 2004. In order to determine the changes occurring in these countries, sigma-convergence (σ) and beta-convergence (β) have been used. The study shows that after 2011 there was a process of convergence among the EU countries in terms of the labour productivity in agriculture.